"One step at a time": Analysing Young Patients' Video Diaries in an Ethnographic Tracing of Fixed Appliances. (4th August 2016) - Wickström, Anette
Abstract : The present article examines children's and young people's experiences of receiving state‐financed orthodontic treatment. Using video diaries and follow‐up interviews, the aim was to explore how fixed appliances act on patients' bodies and social life. The combination of methods reveals complex experiences. The main narrative, primarily found in the interviews, presents a vision of an improved bite that patients and orthodontists share. In the video diaries, a parallel narrative of extended bodily hardship is revealed. Owing to the step‐by‐step process where appliances are gradually tightened, the young patients manage to bear the treatment. However, they cannot foresee its extension.